2015
DOI: 10.1016/j.rpemd.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of condylar position by CBCT after static and dynamic registration in edentulous patients

Abstract: r e v p o r t e s t o m a t o l m e d d e n t c i r m a x i l o f a c . 2 0 1 5;5 6(1):9-17 Cone beam computed tomography Stomatognatic system a b s t r a c t Objectives: The aims of this study are to: compare the condylar position in articular fossa after static and dynamic registration; analyze symmetry between right and left condyles and examine the relationship between articular eminence and condylar position.Methods: Twenty completely edentulous patients were included in this study, after signing a writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Some studies 16,19,36,52,53 have reported that graphic CR recording techniques represent a valid reference as a comparison parameter, because the patient must perform lateral and protrusive movements to apply them. Their reproducibility tends to be more reliable, considering that there is an orthoprosthetic (muscular) balance, which requires the patient to master the movements of the mandibular jaw 33,58,59 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies 16,19,36,52,53 have reported that graphic CR recording techniques represent a valid reference as a comparison parameter, because the patient must perform lateral and protrusive movements to apply them. Their reproducibility tends to be more reliable, considering that there is an orthoprosthetic (muscular) balance, which requires the patient to master the movements of the mandibular jaw 33,58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Their reproducibility tends to be more reliable, considering that there is an orthoprosthetic (muscular) balance, which requires the patient to master the movements of the mandibular jaw 33,58,59 . As in a study by Veloso et al, 19 the EOGA technique was selected as a control compared to other techniques because the externally placed steel plates eased the visualization of the graphic trace 54 . When placed intraorally, it is impossible for the professional to visually follow the trace during the mandibular movements performed by the patient 19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations